THE DESCRIPTION OF SELF CONTROL IN PERPETRATORS OF CYBERBULYING - Anastasya, Yara Andita; Julistia, Rini; Astuti, Widi (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2023)
The use of technology and information can increase the risk of the phenomenon of cyberbullying. One of the factors of cyberbullying is self-control. Individuals with high self-control will be able to instruct and control themselves in facing unexpected situations. In contrast, individuals with low self-control lack instruction and control for themselves; hence they tend to behave negatively. This study engaged a descriptive quantitative method using a cluster random sampling of 100 students. The instrument used in this study was a self-control scale. The data were analyzed by engaging descriptive analysis. The result shows that perpetrators of cyberbullying have moderate self-control. High self-control indicates that students can control their behavior, cognition, and decision. Thus, they can control their behavior in various situations to obtain positive consequences. Low self-control indicates that students do some unacceptable actions to their environment, especially in school. The higher self-control is, the lower the negative behavior individuals will take. Suboptimal self-control is caused by low aspects of self-control in behavior, cognition, and decision. The lowest aspect is behavior control, which means that perpetrators of cyberbullying tend to spend time with their peers. Therefore, self-control does not work optimally.